Teacher Stress and Psychosocial Factors in Teachers from Latin America, North America and Europe - Alvites-Huamaní, Cleofé Genoveva (2019)
In an fast-paced world like that of these days, in which information and knowledge change in thousandths of seconds, and therefore education at all levels must adapt to this. Teachers, who are at the center, must carry out all their activities urgently due to media pressure in their environment, the pressure from authorities, coworkers and even their students. This  can lead to stress over time, that is why this research focused on relating stress and psychosocial factors in teachers from Latin America, North America and Europe, involving in a non-probabilistic sample  n = 81 teachers from different countries, at basic education and university levels. The Teaching Scale (ED-6 α = 0.932) and the Questionnaire of Psychosocial Factors at Academic Work (FPSIS α = 0.916) were used for the data collection, with a non-experimental, correlational, cross-sectional to quantitative approach design. The results obtained indicate that there is a significant correlation between teacher stress and psychosocial factors, (p = .000), prevailing mostly the level of stress due to anxiety, depression, and non-adaptive beliefs that correlate with the psychosocial factors.